MEASUREMENTS AND PERCEPTIONS OF WRITING DEVELOPMENT: OMANI ACADEMIC WRITERS IN ENGLISH - Ewen Arnold (Indonesian JELT, 2008)
Using collaborative research methodology, this study reports on the writing development of a number of Omani teachers of English studying for a UK BA degree in Oman.  It identifies the most useful criteria for measuring writing development, critiquing some previous measures. The measurements with the students’ own perceptions of their development as writers were compared and the two ways of tracking writing development were evaluated. The discussion deals with some of the problems of interpreting data in the light of experience and background knowledge. It analyses some findings concerning the relationship between grammatical complexity and accuracy, and highlights the importance of affective factors in academic writing skills development. Keywords: Collaborative research methodology; Grammatical complexity; Grammatical accuracy; Affective factors; Academic writing skills development.